Rapid prototyping : principles and applications. - Chua, C. K., ....-; Leong, K. F., ....-; Lim, C. S., ....- (New Jersey : World Scientific, 2003)
Rapid Prototyping (RP) has revolutionized the landscape of how prototypes and products are made and small batch manufacturing carried out. This book gives a comprehensive coverage of RP and rapid tooling processes, data formats and applications. A CD-ROM, included in the book, presents RP and its principles in an interactive way to augment the learning experience. Contents: Rapid Prototyping Process Chain Liquid-Based Rapid Prototyping Systems Solid-Based Rapid Prototyping Systems Powder-Based Rapid Prototyping Systems Rapid Prototyping Data Formats Applications and Examples Evaluation and Benchmarking
Keywords: Rapid prototyping